Fritsch–Buttenberg–Wiechell rearrangement of magnesium alkylidene carbenoids leading to the formation of alkynes - Kimura, Tsutomu; Sekiguchi, Koto; Ando, Akane; Imafuji, Aki (Beilstein Journal of Organic Chemistry, 2021)
A series of 1-heteroatom-substituted vinyl p-tolyl sulfoxides were prepared and treated with organometallic reagents to evaluate which combination of sulfoxides and organometallic reagents yielded alkynes the most efficiently. The use of 1-chlorovinyl p-tolyl sulfoxide and isopropylmagnesium chloride was optimal for this purpose. A variety of 1-chlorovinyl p-tolyl sulfoxides were prepared from carbonyl compounds and chloromethyl p-tolyl sulfoxide and were converted into alkynes via the sulfoxide/magnesium exchange reaction and subsequent Fritsch–Buttenberg–Wiechell (FBW) rearrangement of the resulting magnesium alkylidene carbenoids. The mechanism of the FBW rearrangement of magnesium alkylidene carbenoids was studied by using 13C-labeled sulfoxides and by using DFT calculations.
Keywords: alkyne; 1-chlorovinyl p-tolyl sulfoxide; DFT calculation; Fritsch–Buttenberg–Wiechell rearrangement; magnesium alkylidene carbenoid

Acetylene Chemistry: Chemistry, Biology, and Material Science - Diederich, F.; Stang, P. J.; Tykwinski, R. R. (Wiley-VCH, 2005)

(untitled) - Shaw, R.; Elagamy, A.; Althagafi, I.; Pratap, R. (Org. Biomol. Chem., 2020)

(untitled) - Habrant, D.; Rauhala, V.; Koskinen, A. M. P. (Chem. Soc. Rev., 2010)

(untitled) - Corey, E. J.; Fuchs, P. L. (Tetrahedron Lett., 1972)

(untitled) - Gilbert, J. C.; Weerasooriya, U. (J. Org. Chem., 1979)

(untitled) - Ohira, S. (Synth. Commun., 1989)

(untitled) - Müller, S.; Liepold, B.; Roth, G. J.; Bestmann, H. J. (Synlett, 1996)

(untitled) - Knorr, R. (Chem. Rev., 2004)

(untitled) - Jahnke, E.; Tykwinski, R. R. (Chem. Commun., 2010)

(untitled) - Kimura, T. (Synthesis, 2017)

(untitled) - Satoh, T. (Chem. Rec., 2004)

(untitled) - Kimura, T.; Kobayashi, G.; Ishigaki, M.; Inumaru, M.; Sakurada, J.; Satoh, T. (Synthesis, 2012)

(untitled) - Kimura, T.; Watanabe, M.; Kashiwamura, G.; Sakurada, J.; Satoh, T. (Synthesis, 2013)

(untitled) - Kimura, T.; Fukuda, K.; Kashiwamura, G.; Satoh, T. (Heterocycles, 2015)

(untitled) - Kimura, T.; Kobayashi, G.; Ijima, S.; Saito, S.; Imafuji, A.; Satoh, T. (Heteroat. Chem., 2017)

(untitled) - Satoh, T.; Takano, K.; Ota, H.; Someya, H.; Matsuda, K.; Koyama, M. (Tetrahedron, 1998)

(untitled) - Monenschein, H.; Dräger, G.; Jung, A.; Kirschning, A. (Chem. – Eur. J., 1999)

(untitled) - Braun, M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Kimura, T.; Satoh, T. (Tetrahedron, 2013)

(untitled) - Kimura, T.; Satoh, T. (Tetrahedron Lett., 2013)

(untitled) - Nickon, A. (Acc. Chem. Res., 1993)

(untitled) - Dale, H. J. A.; Nottingham, C.; Poree, C.; Lloyd-Jones, G. C. (J. Am. Chem. Soc., 2021)

(untitled) - Bichler, P.; Chalifoux, W. A.; Eisler, S.; Shi Shun, A. L. K.; Chernick, E. T.; Tykwinski, R. R. (Org. Lett., 2009)

(untitled) - Tykwinski, R. R.; Luu, T. (Synthesis, 2012)

(untitled) - Yang, X.; Languet, K.; Thamattoor, D. M. (J. Org. Chem., 2016)

(untitled) - Curtin, D. Y.; Flynn, E. W.; Nystrom, R. F. (J. Am. Chem. Soc., 1958)

(untitled) - Bly, R. S.; Zhong, Z.; Kane, C.; Bly, R. K. (Organometallics, 1994)

Density Functional Theory: Principles, Applications and Analysis - Kimura, T. (Applications of Density Functional Theory Calculations to Lithium Carbenoids and Magnesium Carbenoids, 2013)

(untitled) - Kimura, T.; Satoh, T. (J. Organomet. Chem., 2012)

(untitled) - Wang, B.; Deng, C. (Chem. Phys. Lett., 1988)

(untitled) - Campos, P. J.; Sampedro, D.; Rodríguez, M. A. (Organometallics, 1998)

(untitled) - Pratt, L. M.; Nguyen, N. V.; Kwon, O. (Chem. Lett., 2009)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2013)

Jmol: an open-source Java viewer for chemical structures in 3D

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Peng, C.; Ayala, P. Y.; Schlegel, H. B.; Frisch, M. J. (J. Comput. Chem., 1996)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Chem. Phys., 1989)

(untitled) - Gonzalez, C.; Schlegel, H. B. (J. Phys. Chem., 1990)

(untitled) - Drabowicz, J. (Synthesis, 1986)

(untitled) - Mouriès, V.; Waschbüsch, R.; Carran, J.; Savignac, P. (Synthesis, 1998)